Judgment prey - Sandford, John, 1944 February 23- (G.P. Putnam's Sons, 2023)
"Alex Sand was spending the evening at home playing basketball with his two young sons when all three were shot in cold blood. A wealthy federal judge, there's no short list of people who could have a vendetta against Sands, but the gruesome murders, especially that of his children, turn their St. Paul community on its head. Sand was on the verge of a major donation to a local housing charity, Heart/Twin Cities, and with the money in limbo, eyes suddenly turn to his grieving widow, Margaret Cooper, to see what she might do with the money. Margaret, distraught over the death of her family, struggles to move forward, and can't imagine how or why anyone would target her husband. With public pressure mounting and both the local police force and FBI hitting dead end after dead end, Lucas Davenport and Virgil Flowers are called in to do what others could not: find answers. With each potential lead flawed, Davenport and Flowers are determined to chase every theory until they figure out who killed the Sands. But when they find themselves being stonewalled by the most unlikely of forces, the two wonder if perhaps each misdirection could lead them closer to the truth"--
Keywords: Davenport, Lucas -- (Fictitious character) -- Fiction; Flowers, Virgil -- (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Detective and mystery fiction; Novels